IMKONIYATI CHEKLANGAN O‘QUVCHILARGA FIZIKA FANINI O‘QITISHDA INTERFAOL TEXNOLOGIYALARNI QO‘LLASH - Asammadinova, U. (SCIENCE and SOCIETY, 2025)
The article is dedicated to the role of inclusive education in teaching physics using interactive technologies. It discusses various approaches and tools such as virtual laboratories, interactive whiteboards, mobile applications, and augmented reality, which help create an accessible learning environment for students with special educational needs (SEN). The article emphasizes the importance of adapting the educational process to meet the individual needs of students and overcoming barriers associated with traditional teaching methods. Interactive tools improve material absorption and ensure the active involvement of all students in the learning process.
Keywords: inclusive education; physics; interactive technologies; virtual laboratories; inclusive teaching; special educational needs; mobile applications; augmented reality; educational accessibility